Low-Cost Portable Pupilometer for Circadian Rhythm Studies - Guevara, Edgar; Hernández-Barrios, Ingrid Ameyalli (Revista Mexicana de Ingenieria Biomedica, 2024)
Given the price tag of commercially available devices, developing a low-cost, portable pupilometer based on the Raspberry Pi platform is significant for advancing clinical and research applications in neurology and circadian rhythm studies. This study aimed to design and characterize a pupilometer capable of assessing pupillary light response (PLR) to different wavelengths and its relationship with circadian cycles. Using a Raspberry Pi, a no-infrared filter (NoIR) camera, and custom software, the device was tested on a healthy 24-year-old female subject over 20 days, measuring responses to 635 nm (red) and 463 nm (blue) light stimuli at two daily intervals (8:00 AM and 8:00 PM) in both eyes. Results showed that blue light induced greater pupillary constriction than red light (F(1)= 284.37, p=6.9e-27), with more pronounced responses in the morning (F(1)=12.02, p=0.001), likely due to higher parasympathetic activity. Significant lateral asymmetry (F(1)=12.36, p=0.0008) was also observed in the pupillary response to blue light, suggesting potential intracranial factors. These findings demonstrate the pupilometer’s efficacy in capturing detailed pupillary dynamics, proposing its utility to evaluate pupillary light response in connection with circadian rhythms and lateral asymmetry, providing an affordable solution.